The β-Lactamase Gene Profile and a Plasmid-Carrying Multiple Heavy Metal Resistance Genes of Enterobacter cloacae - Chongyang Wu; Chaoqin Lin; Xinyi Zhu; Hongmao Liu; Wangxiao Zhou; Junwan Lu; Licheng Zhu; Qiyu Bao; Cong Cheng; Yunliang Hu (International Journal of Genomics)
In this work, by high-throughput sequencing, antibiotic resistance genes, including class A (blaCTX-M, blaZ, blaTEM, blaVEB, blaKLUC, and blaSFO), class C (blaSHV, blaDHA, blaMIR, blaAZECL-29, and blaACT), and class D (blaOXA) β-lactamase genes, were identified among the pooled genomic DNA from 212 clinical Enterobacter cloacae isolates. Six blaMIR-positive E. cloacae strains were identified, and pulsed-field gel electrophoresis (PFGE) showed that these strains were not clonally related. The complete genome of the blaMIR-positive strain (Y546) consisted of both a chromosome (4.78 Mb) and a large plasmid pY546 (208.74 kb). The extended-spectrum β-lactamases (ESBLs) (blaSHV-12 and blaCTX-M-9a) and AmpC (blaMIR) were encoded on the chromosome, and the pY546 plasmid contained several clusters of genes conferring resistance to metals, such as copper (pco), arsenic (ars), tellurite (ter), and tetrathionate (ttr), and genes encoding many divalent cation transporter proteins. The comparative genomic analyses of the whole plasmid sequence and of the heavy metal resistance gene-encoding regions revealed that the plasmid sequences of Klebsiella pneumoniae (such as pKPN-332, pKPN-3967, and pKPN-262) shared the highest similarity with those of pY546. It may be concluded that a variety of β-lactamase genes present in E. cloacae which confer resistance to β-lactam antibiotics and the emergence of plasmids carrying heavy metal resistance genes in clinical isolates are alarming and need further surveillance.